Sperm selection techniques in assisted reproduction: a comprehensive review - Arunkumar, Sowbarnika; Thanikachalam, Puvithra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Sperm selection plays a pivotal role in assisted reproductive technology (ART), directly influencing fertilization rates, embryo development and overall clinical outcomes. While conventional methods such as swim-up and density gradient centrifugation methods are in clinical practice, they offer limited precision in identifying spermatozoa with optimal functional ability and DNA integrity. In response to these limitations, a range of advanced sperm selection techniques has emerged, aiming to improve the selection of high-quality spermatozoa. This review explores the principle, methodologies and clinical evidence behind both established and emerging sperm selection methods. Techniques discussed include magnetic-activated cell sorting (MACS), microfluidic sperm sorting (MSS), hyaluronic acid binding assay/ physiological intracytoplasmic sperm injection (HBA/PICSI) and high-magnification selection methods like intracytoplasmic morphologically selected sperm injection (IMSI). Additionally, novel technologies such as Raman spectroscopy, polarized light microscopy and surface charge-based selection (Zeta potential) are examined for their potential applications in reproductive medicine. While early results suggest these advanced methods may enhance ART outcomes, particularly in cases of male factor infertility, further large-scale randomized controlled trials are needed to confirm their clinical utility and define their optimal use. This review aims to provide ART practitioners with a comprehensive overview of the evolving landscape of sperm selection in ART, highlighting both current practices and future directions.